Exclusive Image Gallery on Human Spinal Cord Regeneration-Clinical Image-42 - Giselher Schalow (Imaging Journal of Clinical and Medical Sciences - Peertechz Publications, 2019)
Up and down movements of the trunk to arch the patient's back and to activate neurogenesis at the SCI level Th10. The impaired arch is marked with SCI Th10.